2017
DOI: 10.1111/jfd.12743
|View full text |Cite
|
Sign up to set email alerts
|

Transmission of a common intestinal neoplasm in zebrafish by cohabitation

Abstract: Intestinal neoplasms are common in zebrafish (Danio rerio) research facilities. These tumours are most often seen in older fish and are classified as small cell carcinomas or adenocarcinomas. Affected fish populations always contain subpopulations with preneoplastic lesions, characterized by epithelial hyperplasia or inflammation. Previous observations indicated that these tumours are unlikely caused by diet, water quality or genetic background, suggesting an infectious aetiology. We performed five transmissio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
51
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(56 citation statements)
references
References 61 publications
5
51
0
Order By: Relevance
“…With our present study with zebrafish, the occurrence of the intestinal neoplasms in many cases and facilities in which the worms were absent shows that, while strongly linked, the presence of the worm is not required to develop these lesions. This agrees with laboratory transmission experiments in which the intestinal neoplasms were transmitted in the absence of the worms (Burns et al., 2018). The aetiology of neoplasia is often multifactorial, and whereas the P. tomentosa may not be the primary initiator, it is apparently an effective promoter following exposure to another agent, as the Mycoplasma sp.…”
Section: Worm Positive Worm Negative Row Totalssupporting
confidence: 91%
See 2 more Smart Citations
“…With our present study with zebrafish, the occurrence of the intestinal neoplasms in many cases and facilities in which the worms were absent shows that, while strongly linked, the presence of the worm is not required to develop these lesions. This agrees with laboratory transmission experiments in which the intestinal neoplasms were transmitted in the absence of the worms (Burns et al., 2018). The aetiology of neoplasia is often multifactorial, and whereas the P. tomentosa may not be the primary initiator, it is apparently an effective promoter following exposure to another agent, as the Mycoplasma sp.…”
Section: Worm Positive Worm Negative Row Totalssupporting
confidence: 91%
“…Pseudocapillaria tomentosa penetrates the epithelium and causes severe, chronic inflammation in both diagnostic cases (Murray & Peterson, 2015) and in experimental studies (Gaulke et al., 2019). This provides an explanation for the correlations seen in our retrospective study and the observation that that tumours developed within populations of fish with P. tomentosa after about 3 months exposure (Gaulke et al., 2019) versus about 9 months without the worms (Burns et al., 2018). It is possible that the nematode and the Mycoplasma sp.…”
Section: Worm Positive Worm Negative Row Totalssupporting
confidence: 67%
See 1 more Smart Citation
“…based on examination of tissues from each intestine. Following our previous study [22], two broad categories, inflammation and hyperplastic changes, were scored in zebrafish intestines. A total histopathology score, which is the sum of the inflammation and hyperplasia scores, was also calculated.…”
Section: Methodsmentioning
confidence: 99%
“…Indeed, our recent review of the ZIRC diagnostic case database revealed that the worm was present in only about one‐fourth of the facilities or cases in which intestinal neoplasia was diagnosed. Burns et al (2018) showed that some intestinal carcinomas are naturally transmitted by either co‐habitation with or exposure to effluent from affected fish. They also correlated neoplasms with the presence of a specific mycoplasma's 16S rDNA sequence that was close to M. penetrans .…”
Section: Overview Of Diseasesmentioning
confidence: 99%